An Analysis of English Summative Test Used at Grade Eleven of Madrasah Aliyah (MA) Bina Cendekia Tampo - Moneterisqi, Hiqma; Rohmana, Rohmana; Fatmawati, Wa Ode (Journal of Teaching of English, 2021)
This research aims to investigate the quality of English summative test at grade eleven of Madrasah Aliyah (MA) Bina Cendekia Tampo. The design of this research was descriptive quantitative research. In analyzing the data, the researcher used quantitative analysisusing the SPSS 25.0 program and Microsoft Excel to operate data in terms of item validity, the level of difficulty, discrimination power,item of distractors and reliability of the test. The result of the research shows that : (1) In term of validity, there are 12 items (30%) considered valid and 28 items (70%) are considered invalid; (2) In term of level of difficulty, there are 15 items of the test (37,5%) categorized as too difficult, 13 items of the test (32,5%) are categorized as moderate and 12 items (30%) are categorized as too easy; (3) In term of discrimination power, there are 3 items (7,5%) categorized as excellent, 10 items (25%) are categorized as good, 8 items (20%) are categorized as satisfactory, 17 items (42,5%) are categorized as poor and 2 items (5%) are categorized as very poor; (4) In term of item of distractor, there are 27 items (67,5%) categorized as effective and 13 items (32,5%) are categorized ineffective; (5) In term of reliability aspect, the test has high reliability with r11 of the test is 0,775; (6) Based on the overall analysis, there are 3 items of the test categorized as excellent, 10 items of the test are categorized as good, 9 items of the test are categorized assatisfactory, 13 items of the test are categorized as poor and 5 items of the test are categorized as very poor. In conclusion, most of the items in English summative of Madrasah Aliyah (MA) Bina Cendekia Tampo do not fulfill the quality of a good test.